Numerical investigation of disk bypass pipeline inspection gauge with hole in disk - Rabby, Md Insiat Islam; Masuri, Siti Ujila; Samsul Kamal, Ahmad Syakir Fariz; Bin Hairuddin, Abdul Aziz (Elsevier, 2024)
Bypass Pipeline Inspection Gauges (PIGs) are widely employed as the most effective and economical devices for pipeline cleaning, maintenance, and inspection operations. The speed of these bypass PIGs significantly impacts the operational activities of pipelines. Very high or low PIG speeds may cause damage to the pipeline and the PIG itself. Therefore, it is important to control the speed of the PIG for better pigging operations. This study focuses on the influencing parameters and their impact on PIG speed. The approach of Computational Fluid Dynamics (CFD) has been utilized to model fully turbulent flow around a sample of a disk bypass PIG with a hole in the disk section for four different cases. PIG speed and pressure loss coefficient are measured to evaluate the effectiveness of the PIG. Meanwhile, two dimensionless groups are introduced based on the influencing design parameters for the movement of the disk bypass PIG, with and without a hole, to measure the optimal design parameters. The results show that a disk bypass PIG with a hole in the disk provides 5%-7% better results in terms of PIG speed and 6%-9% for the pressure loss coefficient around the PIG section. Among the four cases of a disk bypass PIG with a hole in the disk section, case-1 shows better pigging operation, with a dimensionless group value of 0.24. However, case-1 exhibits a 2.7%-22% reduction in PIG speed and a 12%-72% reduction in the pressure loss coefficient compared to other cases. Additionally, the lowest value of the presented dimensionless group indicates better pigging operation, and the optimal value of the dimensionless group is 0.24 for the design consideration of the PIG. This study holds directional significance for the design of the structural parameters of the PIG, which are useful for pipeline clean-up, inspection, and operational maintenance, and it provides reference value for related researches.